2020
DOI: 10.1093/cid/ciaa615
|View full text |Cite
|
Sign up to set email alerts
|

Withholding Primary Pneumocystis Pneumonia Prophylaxis in Virologically Suppressed Patients With Human Immunodeficiency Virus: An Emulation of a Pragmatic Trial in COHERE

Abstract: Background Using data from the COHERE collaboration, we investigated whether primary prophylaxis for Pneumocystis Pneumonia (PcP) might be withheld in all patients on antiretroviral therapy with suppressed plasma HIV RNA (≤ 400c/mL) irrespective of CD4 count. Methods We implemented an established causal inference approach whereby observational data is used to emulate a randomised trial. Patients taking PcP prophylaxis were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
2
13
0
2
Order By: Relevance
“…In patients in this CD4 count stratum, with plasma HIV RNA below 400 copies/ML and off prophylaxis the incidence of primary PjP was 12 (95% CI 2 to 45) events per 1000 person‐years (py). A more recent analysis pointed towards safety of discontinuing prophylaxis even in all patients that achieve undectable plasma HIV‐RNA levels [16]. Similar findings were reported by smaller cohorts [17‐19], a randomized trial [20] and in two systematic reviews [21,22].…”
Section: Introductionsupporting
confidence: 68%
“…In patients in this CD4 count stratum, with plasma HIV RNA below 400 copies/ML and off prophylaxis the incidence of primary PjP was 12 (95% CI 2 to 45) events per 1000 person‐years (py). A more recent analysis pointed towards safety of discontinuing prophylaxis even in all patients that achieve undectable plasma HIV‐RNA levels [16]. Similar findings were reported by smaller cohorts [17‐19], a randomized trial [20] and in two systematic reviews [21,22].…”
Section: Introductionsupporting
confidence: 68%
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…One-hundred and fifteen studies (58%) completely reported how the target trial protocol was emulated. Eighty-seven studies (44%) provided both the protocol of the target trial and described how it was emulated (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of the approach is that we assume a fixed censoring point 𝜏, primarily to enable us to use standard results for the theoretical work. Having a fixed censoring point is unusual in individual patient randomized trials, but can occur in cluster randomized trials where interventions start on a specific day, and is most often the case, by design, for emulated trials using observational data (Atkinson et al (2020)). Notwithstanding these examples, most clinical trials have rolling recruitment and stop at a fixed calendar time, which means that the censoring time is variable.…”
Section: Discussionmentioning
confidence: 99%